Research of single-shaft turbojet engine starting - Кулик, Н. С.; Моисеев, Б. М.; Панин, В. В.; Ратынский, В. В. (Proceedings of National Aviation University (archive), 2000)
Results of experimental research of influence of different types of malfunction of turbojet engine RU19A-300 main units upon the working process parameters on the start are represented. It is shown that essential scatter of values of dynamic parameter complexes exists for the identical rotational frequencies of the rotor on different stages of start, that makes difficult identification of malfunction "images" on this non-steady mode